If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6q + 4 = 2q + 28 Reorder the terms: 4 + 6q = 2q + 28 Reorder the terms: 4 + 6q = 28 + 2q Solving 4 + 6q = 28 + 2q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-2q' to each side of the equation. 4 + 6q + -2q = 28 + 2q + -2q Combine like terms: 6q + -2q = 4q 4 + 4q = 28 + 2q + -2q Combine like terms: 2q + -2q = 0 4 + 4q = 28 + 0 4 + 4q = 28 Add '-4' to each side of the equation. 4 + -4 + 4q = 28 + -4 Combine like terms: 4 + -4 = 0 0 + 4q = 28 + -4 4q = 28 + -4 Combine like terms: 28 + -4 = 24 4q = 24 Divide each side by '4'. q = 6 Simplifying q = 6
| y+115= | | 2y^2+11h+5=0 | | .18+2X=.17 | | 2b-7=155+2b | | 2x-7=155+2x | | 2y^2+11k+5=0 | | 4(b+2)=20 | | -2(x-3)+5x=36 | | 4x+10+3=40x-3x | | 4+5ln(x)=5 | | 4+ln(5)=5 | | 1.5t^4-3t^2+5t-1=0 | | 44x+3=45x | | x=1.5t^4-3t^2+5t-1 | | 45x+3=45x | | 4/3x-4=-3/4x-4 | | 51z-21=z-58 | | 11x+17=13x-1 | | n-51=24 | | 44x+2=44x+2 | | 5x-29y=-23 | | .7(x+5)+.4(x+25)=30 | | -3(-6n+3)-7n=-86 | | .1428(x+7)+.035(x-28)=x+23 | | x^2+2=102 | | 5b-5-12b-8= | | d(x)=2x-4 | | X=180+0.6(60+0.2x) | | Log(16+2x)=log(x^2-4x) | | X=180+0.6+(60+0.2) | | x^2-39x+376=0 | | X=180+0.6y |